Effects of feed processing on the apparent ileal digestibility of amino acids in pig diets containing wheat bran or wheat middlings - Valaja, Jarmo; Siljander-Rasi, Hilkka; Mäkinen, Markku (Agricultural and Food Science, 1996)
The effects of feed processing on the apparent ileal digestibility of amino acid and the utilisation of nitrogen (N) in diets containing wheat by-products were studied in five castrated male pigs (live weight 40-109 kg). A T-cannula was surgically fitted into the caecum of the pigs at a live weight of 27 kg using the steered ileo-caecal valve technique. The experiment was conducted with a 6 x 5 cyclic change-over design in which six diets were arranged 2x3 factorially. The corresponding factors were type of wheat by-product in the diets: wheat bran (152 g/kg) or wheat middlings (328 g/kg), and method of feed processing: steam pelleting, expanding or extrusion. The other dietary feed ingredients were barley and soya bean meal. The feed-processing method or dietary wheat by-product had no effect on the apparent ileal digestibility of amino acids and crude protein. The pigs on diets containing wheat middlings tended to retain more N per intake (p<0.10) than did those on wheat bran diets. The wheat middlings diets also tended to have higher biological values than did the wheat bran diets (p<0.10). Further, daily N retention tended to be better with expanding than with pelleting (p<0.10). The N retention differences were mainly caused by the differences in N intakes of the treatments. In conclusion, feed processing at a moderate temperature or wheat by-product in the diets had no influence on the apparent ileal digestibility of amino acids.